Analysis of the Need for Developing a Learning Guidebook Based On Character Values: An Effort to Create a School Environment with Character - Agustini, Rianti (BIRCU, 2024)
Character education is an important thing that must be implemented, especially in the school environment. Character values will guide students in life. In line with this, this research aims to determine the analysis of the needs for developing a character values guidebook created by school principals in realizing schools with character. This type of research is development research. This research is limited by discussing the analysis stages in the ADDIE model. Data was obtained from observations and interviews conducted at MTs YAPI Sleman. The results of the research show that teachers really want a guidebook for implementing character education which is accompanied by tips for implementing character education